Perbandingan antara Energi Meter Berbasis ESP32+PZEM004 dengan Smart Plug Komersial: The Comparison between the Energy meter based on ESP32+PZEM004 vs Commercial Smart Plug - Suwarno, Djoko (ReTII, 2025)
Electric Energy consumption monitoring is an important process to improve energy efficiency. Today, there are two approaches to energy monitoring: first in build an energy meter using ESP32 and PZEM-004T module, and second is using a commercial smart plug. This paper compares those approaches in accuracy, features, flexibility, price, and complexity. Based on the result and discussion, results ESP32+PZXEM 004T system performs better in flexibility as needed. On the other hand, commercial smart plugs give easyly in use (plug and play). Better integration in the smart home ecosystem and a smooth Graphical User Interface. An energy meter developed shows measure parameters, ie, voltage (V), currents (A), Power factor, real power (W), apparent power (VA), energy (Wh), frequency (Hz), and time ON, energy meter was built to measure usage energy for electric devices for short-term usage.